2018
DOI: 10.1002/2017gl076070
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Sea Surface Displacement and Fault Slip Distribution of the 2017 Tehuantepec Earthquake (Mw 8.2) in Mexico Estimated From Tsunami Waveforms

Abstract: The 2017 Tehuantepec earthquake (Mw 8.2) was the first great normal fault event ever instrumentally recorded to occur in the Middle America Trench. The earthquake generated a tsunami with an amplitude of 1.8 m (height = 3.5 m) in Puerto Chiapas, Mexico. Tsunami waveforms recorded at coastal tide gauges and offshore buoy stations were used to estimate the optimum sea surface displacement without assuming any fault. Our optimum sea surface displacement model indicated that the maximum uplift of 0.5 m is located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Fault patches with >1‐m slip can be divided into two along‐strike segments, separated by the TFZ (Figure c). A large slip patch peaks at 55 km along strike at 30‐km depth with maximum slip of 9.5 m, which is consistent with other slip models derived from the seismic data (Jiménez, ; Okuwaki & Yagi, ; Ye et al, ), but is shallower than the slip peak at 60‐km depth in a slip model derived from tsunami data (Gusman et al, ). The breaking of this slip patch, spanning a depth range of 10–70 km, releases most of the seismic moment.…”
Section: Ffmsupporting
confidence: 86%
See 1 more Smart Citation
“…Fault patches with >1‐m slip can be divided into two along‐strike segments, separated by the TFZ (Figure c). A large slip patch peaks at 55 km along strike at 30‐km depth with maximum slip of 9.5 m, which is consistent with other slip models derived from the seismic data (Jiménez, ; Okuwaki & Yagi, ; Ye et al, ), but is shallower than the slip peak at 60‐km depth in a slip model derived from tsunami data (Gusman et al, ). The breaking of this slip patch, spanning a depth range of 10–70 km, releases most of the seismic moment.…”
Section: Ffmsupporting
confidence: 86%
“…Using the global seismic data, Okuwaki and Yagi (2017) found that the 2017 Chiapas earthquake mainly ruptured shallower than 50 km. However, a deep, major rupture located with a depth range of 40-60 km is inverted by fitting the tsunami data (Gusman et al, 2017). To reduce the nonuniqueness of inversion, Ye et al (2017) jointly inverted teleseismic and tsunami data for the earthquake, which has the main rupture from 30-70-km depth, with the rupture speed of 3 km/s constrained by rupture directivity and backprojection of one regional seismic network.…”
Section: 1029/2018gl080009mentioning
confidence: 99%
“…The 8 September 2017 M8.2 Tehuantepec, Mexico, earthquake ruptured an~150-km high-angle normal fault below the subduction zone megathrust (Chen et al, 2018;Gusman et al, 2018;Ye et al, 2017), from a depth of 20 to 80 km with upward of 12 m of slip ( Figure 1) and with the majority of moment release at~50-km depth. The event is somewhat peculiar because of its mechanism, dominated by extensional stresses within a convergent plate boundary, and because its deep extent implies complete rupture of the lithosphere .…”
Section: The Tehuantepec Earthquake and Tsunamimentioning
confidence: 99%
“…Observed tsunami waveforms can be used to estimate the sea surface displacement initiating the tsunami through an inversion analysis based on a linear superposition of unit sources. Without a fault model, these unit sources at the sea surface are typically expressed by auxiliary basis functions (Gusman et al, ; Saito et al, ; Satake et al, ). This approach accurately reproduces the observed tsunami waveforms, especially when high‐resolution Green's functions are considered (Baba et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Such locations can be determined using an optimization method. The same technique has been applied to several tsunami events such as the 2011 Tohoku‐oki tsunami (Mulia & Asano, ), the 2012 Haida Gwaii tsunami (Gusman et al, ), and the 2017 Tehuantepec tsunami (Gusman et al, ). The method provides advantages over the conventional tsunami source inversion with equidistant unit sources, but it requires the computation of synthetic waveforms for each iteration.…”
Section: Introductionmentioning
confidence: 99%